Ideological differences in the expanse of the moral circle - Waytz, Adam; Iyer, Ravi; Young, Liane; Haidt, Jonathan; Graham, Jesse (Nature communications, 2019)
Do clashes between ideologies reflect policy differences or something more fundamental? The present research suggests they reflect core psychological differences such that liberals express compassion toward less structured and more encompassing entities (i.e., universalism), whereas conservatives express compassion toward more well-defined and less encompassing entities (i.e., parochialism). Here we report seven studies illustrating universalist versus parochial differences in compassion. Studies 1a-1c show that liberals, relative to conservatives, express greater moral concern toward friends relative to family, and the world relative to the nation. Studies 2a-2b demonstrate these universalist versus parochial preferences extend toward simple shapes depicted as proxies for loose versus tight social circles. Using stimuli devoid of political relevance demonstrates that the universalist-parochialist distinction does not simply reflect differing policy preferences. Studies 3a-3b indicate these universalist versus parochial tendencies extend to humans versus nonhumans more generally, demonstrating the breadth of these psychological differences. How do liberals and conservatives differ in their expression of compassion and moral concern? The authors show that conservatives tend to express concern toward smaller, more well-defined, and less permeable social circles, while liberals express concern toward larger, less well-defined, and more permeable social circles.